Mandatory IFRS adoption and managers' compensation: the moderating effect of corporate governance. (2017) - Wali, Senda; Kamel, Olfa
Our study aims to examine the effect of the mandatory IFRS adoption on executive compensation and the moderating effect of corporate governance in an emerging context, such as the case of Malaysia. Based on a sample of 96 companies listed on the stock exchange of Malaysia ( bursa Malaysia ), the results obtained from the various tests indicate that there is not significant effect between the IFRS adoption and managers compensation in Malaysia. Empirical evidence shows also that some corporate governance mechanisms moderate the relationship between IFRS adoption and executive compensation. Particularly, the independence of the nominating committee, compensation committee size and independence has a moderating effect on the relationship between IFRS and changes in compensation.